2009
DOI: 10.1002/rra.1253
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of hydrologic and geomorphic changes affecting a shrinking mire

Abstract: The Kushiro Mire in subarctic Japan has significantly reduced in size because of the complex interaction of many processes, including snowmelt runoff, sediment transport and vegetation dynamics. This study uses a coupled integrated catchment-based eco-hydrology model with a mass transport process (NICE-MASS) to investigate the influence of hydrologic and geomorphic changes on the Kushiro Mire. Coefficients of the sediment-rating curve in the snowmelt runoff are very different from those in the snow-free period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Up to now, the author has developed the distributed NICE model series (Nakayama, 2007(Nakayama, , 2008Nakayama and Watanabe, 2004, 2008aNakayama et al, , 2007, which includes surface-unsaturated-saturated water processes and assimilates land-surface processes describing variations of LAI (leaf area index) and FPAR (fraction of photosynthetically active radiation) derived from MODIS satellite data (Fig. 2).…”
Section: Nice Model Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, the author has developed the distributed NICE model series (Nakayama, 2007(Nakayama, , 2008Nakayama and Watanabe, 2004, 2008aNakayama et al, , 2007, which includes surface-unsaturated-saturated water processes and assimilates land-surface processes describing variations of LAI (leaf area index) and FPAR (fraction of photosynthetically active radiation) derived from MODIS satellite data (Fig. 2).…”
Section: Nice Model Seriesmentioning
confidence: 99%
“…The author expanded the process-based NICE (NIES Integrated Catchment-based Eco-hydrology) model series (Nakayama, 2007(Nakayama, , 2008Nakayama and Watanabe, 2004, 2008aNakayama et al, , 2007 to include mass transport and vegetation succession processes in the Kucyoro River catchment, Japan (NICE-VEG). In the first step of applying the model to this objective, it is important to distinguish two dominant vegetation types in the Kushiro Mire, socalled, between invasive alder (shrub forest) and species indigenous to the mire (reed-sedge vegetation).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the sediment content (ash content) and elevation were highest at the upper river. Nakayama (2010) reported that these area increased elevation by sedimentation. From these results, the large effect on the alder tree height, such as from sediment inflow from rivers, a change in elevation, and the water table drawdown caused by a high sediment content may be restricted to the area of sediment deposition in the inflow area or to the river banks where previous research was carried out.…”
Section: Environmental Factors Controlling the Alder Treesmentioning
confidence: 96%
“…7). These differences were related to channelization and land-use change in the upper basin which caused aggradation and elevation change in the mire (Nakayama, 2010). This change would cause an immediate drying out of the alder sites, which was indicated by the time of water table drawdown.…”
Section: Flooding Indicesmentioning
confidence: 98%
See 1 more Smart Citation